A journey of collaborative learning organization research: Interview with Victoria Marsick and Karen Watkins. Issue 3 (9th April 2018) - Sidani, Yusuf; Reese, Simon
Abstract : Purpose: This paper aims to provide an overview of the development of learning organization concepts from the perspectives of Dr Victoria Marsick and Dr Karen Watkins and presents an interesting evolution of their work together spanning over three decades. Design/methodology/approach: Through a conversation with thought-leading scholars Dr Victoria Marsick and Dr Karen Watkins, this paper discussed serval topics pertaining to the evolution of the learning organization debate and provides their unique perspective on the development of their theories. Findings: The learning organization debate has many foundations that today have led to differing perspectives, which Dr Marsick and Dr Watkins advocate. They developed their learning organization concepts from their particular background, which varies from others. To these thought leaders, cultural aspects are the critical focus of the learning organization. Originality/value: The discussion with Victoria Marsick and Karen Watkins reveals their understanding of the evolution of the contested discussion around learning organization definition and implications. The understanding of this evolution, in their words, provides context for researchers and practitioners.